Motivational interviewing for smoking cessation. - Lai, D; Cahill, K; Qin, Y; Tang, J (2010)
BACKGROUND: Motivational Interviewing (MI) is a directive patient-centred style of counselling, designed to help people to explore and resolve ambivalence about behaviour change. It was developed as a treatment for alcohol abuse, but may help smokers to a make a successful attempt to quit. OBJECTIVES: To determine the effects of motivational interviewing in promoting smoking cessation. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group Specialized Register for studies with terms (motivational OR motivation OR motivating OR motivate OR behavi* OR motivat*) and (interview* OR session* OR counsel* OR practi*) in the title or abstract, or as keywords. Date of the most recent search: April 2009. SELECTION CRITERIA: Randomized controlled trials in which motivational interviewing or its variants were offered to smokers to assist smoking cessation. DATA COLLECTION AND ANALYSIS: We extracted data in duplicate. The main outcome measure was abstinence from smoking after at least six months follow up. We used the most rigorous definition of abstinence in each trial, and biochemically validated rates where available. Subjects lost to follow up were treated as continuing smokers. We performed meta-analysis using a fixed-effect Mantel-Haenszel model. MAIN RESULTS: We identified 14 studies published between 1997 and 2008, involving over 10,000 smokers. Trials were conducted in one to four sessions, with the duration of each session ranging from 15 to 45 minutes. All but two of the trials used supportive telephone contacts, and supplemented the counselling with self-help materials. MI was generally compared with brief advice or usual care in the trials. Interventions were delivered by primary care physicians, hospital clinicians, nurses or counsellors. Our meta-analysis of MI versus brief advice or usual care yielded a modest but significant increase in quitting (RR 1.27; 95% CI 1.14 to 1.42). Subgroup analyses suggested that MI was effective when delivered by primary care physicians (RR 3.49; 95% CI 1.53 to 7.94) and by counsellors (RR 1.27; 95% CI 1.12 to 1.43), and when it was conducted in longer sessions (more than 20 minutes per session) (RR 1.31; 95% CI 1.16 to 1.49). Multiple session treatments may be slightly more effective than single sessions, but both regimens produced positive outcomes. Evidence is unclear at present on the optimal number of follow-up calls.There was variation across the trials in treatment fidelity. All trials used some variant of motivational interviewing.Critical details in how it was modified for the particular study population, the training of therapists and the content of the counselling were sometimes lacking from trial reports. AUTHORS' CONCLUSIONS: Motivational interviewing may assist smokers to quit. However, the results should be interpreted with caution due to variations in study quality, treatment fidelity and the possibility of publication or selective reporting bias.